Psychology of Criminal In Conditions Of Socioeconomic System Transformation - Dmitrievna Burkaltseva, Diana; Viktorovich Betskov, Aleksandr; Shapievich Kilyaskhanov, Hizri; Ivanovich Demin, Gennadiy; Leonidovich Grischenko, Leonid; Evgenievna Timoshenko, Oksana; Sergeevich Tyulin, Andrey (Opción, 2019)
Article examines main approaches to psychological characteristics of criminal ac- tivity in the context of the socioeconomic system of transformation. Dialectical, personal and systemic approaches form the study’s framework. Methods of ob- servation, interviews, and analysis applied to study current topic. Existing studies consider features of criminal’s personality from the standpoint of legal, social, de- mographic, criminal characteristics. As a result, psychological concepts replaced by legal ones. Attention paid mostly to general individual’s characteristics thus not allowing getting objective data certain categories of criminals. Correlation between social and biological factors of criminal’s personality still one of the most impor- tant topics of research. Current research gives an overview of foreign and Rus- sian scientists’ researches. General classification of cybercrime designed. Under conditions of the socioeconomic system transformation results of research acquire practical significance. The research will help to create conditions and methods of cybercrime prevention.